The Formation of Antibiotic Resistance Genes in Bacterial Communities During Garlic Powder Processing - Liu, Yanxia; Gao, Peng; Wu, Yuhao; Wang, Xiaorui; Lu, Xiaoming; Liu, Chao; Li, Ningyang; Sun, Jinyue; Xiao, Jianbo; Jesus, Simal-Gandara (Frontiers in Nutrition, 2021)
Chinese garlic powder is exported to all countries in the world, but the excess of microorganisms is a serious problem affecting the export. The number of microorganisms has a serious impact on the pricing of garlic powder. It is very important to detect and control the microorganism in garlic powder. The purpose of this study was to investigate the contamination and drug resistance of microorganisms during the processing of garlic powder. We used metagenomics and Illumina sequencing to study the composition and dynamic distribution of antibiotic resistance genes (ARGs), but also microbial community in three kinds of garlic products from factory processing. The results showed that a total of 126 ARG genes were detected in all the samples, which belonged to 11 ARG species. With the processing of garlic powder, the expression of ARGs showed a trend to increase at first, and then to decrease. Network analysis was used to study the co-occurrence patterns among ARG subtypes and amongst bacterial communities and ARGs.